Klosterflucht und Bittgang Apostasie und monastische Mobilität im 15. Jahrhundert - Svec Goetschi, Milena (Zürcher Beiträge zur Geschichtswissenschaft, 2015)
Religious sometimes broke their vows and returned illegally to the society of the late Middle Ages. The study deals with the most radical violation of the monastic way of life, the escape from the monastery and the apostasy of the religious community. The focus is almost a thousand petitions from the Roman-German Empire. The study of apostasy provides insights into motives, dissemination, prevention and sanctions and explains divergences between norms and practice.